Factors associated with misreporting in performance-based financing in Burkina Faso: implications for risk-based verification - Kuunibe, Naasegnibe; Lohmann, Julia; Schleicher, Michael; Koulidiati, Jean-Louis; Robyn, Paul Jacob; Zigani, Zambendé; Sanon, Adama; De Allegri, Manuela (The international journal of health planning and management, 2019)
Performance-based financing (PBF) has been piloted in many low- and middle-income countries (LMICs) as a strategy to improve access to and quality of health services. As a key component of PBF, quantity verification is carried out to ensure that reported data matches the actual number of services provided. However, cost concerns have led to a call for risk-based verification. Existing evidence suggests misreporting is associated with factors such as complexity of indicators, high service volume, and accepted error margin. In contrast, evidence on the association of key facility characteristics with misreporting in PBF is scarce. We contributed to filling this gap in knowledge by combining administrative data from a large-scale pilot PBF program in Burkina Faso with data from a health facility assessment in the context of an impact evaluation of the intervention. Our results showed the coexistence of both overreporting and underreporting and that misreporting varied by service indicator and health district. We also found that the number of clinical staff at the facility, the population size in the facility catchment area, and the distance between the facility and the district administration were associated with the probability of misreporting. We recommend further research of these factors in the move towards risk-based verification. In addition, given that our analysis identified relevant associations, but could not explain them, we recommend further qualitative inquiry into verification processes.